HyperCube4x: A viewport management system proposal. (April 2023) - Lima, Alessandro Rego de; Carvalho, Diana Carneiro Machado de; Rocha, Tânia de Jesus Vilela da
This article presents a novel management and information visualization system proposal based on the tesseract, the 4D-hypercube. The concept comprises metaphors that mimic the tesseract geometrical properties using interaction and information visualization techniques, made possible by modern computer systems and human capabilities such as spatial cognition. The discussion compares the Hypercube and the traditional desktop metaphor systems. An operational prototype is also available for reader testing. Finally, a preliminary assessment with 31 participants revealed that 81.05% "agree" or "totally agree" that the proposed concepts offer real gains compared to the desktop metaphor.